Experimental study on hygrothermal accelerated aging effects of transparent fire resistive wood structure coatings. Issue 1 (1st February 2022) - Zhang, Tianhao; Huang, Hao; Ge, Xinguo; Zhang, Zejiang; Li, Pingli
Abstract: In this paper, the durability of fire performance of a transparent fire resistive coating for wood structure was studied using hygrothermal accelerated aging. The aging effects was analysed using SEM/EDS and fire test. The results show that after 21 days of aging, the flame-retardant components gradually precipitate to the surface. The coating basically loses its expansion ability and the char layer shows a low-strength lamellar structure. The flame-retardant time of the coating decreased by 43.48% from 23 min to 13 min.